Review: Research progress of adipose-derived stem cells in the treatment of chronic wounds - Hao, Zhuolun; Qi, Wenli; Sun, Jiaming; Zhou, Muran; Guo, Nengqiang (Frontiers in Chemistry, 2023)
Although methods are used to treat wounds clinically, there are still many challenges in the treatment of chronic wounds due to excessive inflammatory response, difficulties in epithelialization, vascularization, and other factors. With the increasing research on adipose-derived stem cells (ADSCs) in recent years, accumulating evidence has shown that ADSCs scan promotes the healing of chronic wounds by regulating macrophage function and cellular immunity and promoting angiogenesis and epithelialization. The present study reviewed the difficulties in the treatment of chronic wounds, as well as the advantages and the mechanism of ADSCs in promoting the healing of chronic wounds, to provide a reference for the stem cell therapy of chronic wounds.